Core Size Interconversions of Au30(S-tBu)18 and Au36(SPhX)24 - Dass, Amala; Jones, Tanya C; Theivendran, Shevanuja; Sementa, Luca; Fortunelli, Alessandro (Journal of physical chemistry. C, 2017)
We report for the first time the interconversion between two nanomolecules: Au36(SPhX)24, (where X = -H or -tBu) and Au30(S-tBu)18. This is accomplished through thermochemical etching, with HSPhX on Au30(S-tBu)18 which converts the nanomolecule to Au36(SPhX)24. We further show that the conversion is reversible from Au36(SPhX)24 to Au30(S-tBu)18 with tert-butyl thiol (HS-tBu) under the same thermochemical conditions. Not only is this the first reported interconversion between two nanomolecules, but this report further demonstrates the conversion from a smaller to a larger sized nanomolecule, which is a rare occurrence. Experimental evidence for the reversible conversion is provided using matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS), nanoelectrospray ionization mass spectrometry (nESI-MS), and UV–vis–NIR spectroscopy. This discovery leads to valuable insight into the inherent nature of ligand dependency on the composition and atomic structure of gold–thiolate nanomolecules. The nanomolecules, Au36(SPhX)24 and Au30(S-tBu)18, have cuboctahedral atomic structures with fcc arrangement but have entirely different staple arrangements, with Au28 and Au20 cores, respectively. Theoretical studies show that the difference between Au30(S-tBu)18 and Au36(SPhH)24 resides in the different fragmentation energy of the two species: conjugation in Au36(SPhH)24 weakens the strength of ligand bonding to the Au cluster and thus makes it somewhat less stable than Au30(S-tBu)18. Furthermore, Au30(S-tBu)18 appears to be slightly more stable than Au36(SPhH)24 also in terms of atomization energy of the Au cluster and ligand/ligand interactions.